Regional nodal irradiation in breast cancer patients: A treatment planning study of the breast cancer working group of the German society of radiation oncology - Duma, Marciana Nona; Borm, Kai; Hehr, Thomas; Piroth, Marc D.; Gerd, Fastner; Baumann, René; Combs, Stephanie E.; Corradini, Stefanie; Dunst, Jürgen; Krug, David; Hörner-Rieber, Juliane; Matuschek, Christiane; et al. (Medical Dosimetry, 2025)
The aim of the study was to analyze the interinstitutional differences in the planning process/approach of regional nodal irradiation (RNI) in breast cancer patients in expert centres. Based on a predefined risk constellation, the left breast and the axillary, periclavicular and internal mammarian lymph node areas had to be irradiated. The study focused on left-sided RNI. One CT dataset (free breathing) each of a regular (R) adipose (A) and a slender patient (S) were centrally selected and all target volumes (CTV: level II, III, IV + internal mammary artery chain region-IMC, left breast, PTV and OARs) were contoured according to the ESTRO recommendations. A total dose of 50.4/1.8 Gy was set as the dosage with free choice of technique/inclinic constraints. Dose files were analyzed centrally as DICOM files (CTV: D95%, D50%, D1% and V95%; OAR: D1%, Dmean, V20Gy, V30Gy, V40Gy and the absolute V95% of normal tissue outside the PTV). A total of 18 data sets were analyzed. Differences of almost 10 Gy in TV coverage were significant ( p < 0.05). This was evident between patients e.g., for CTV_IMC D95%/D50% S:47.1Gy ± 1.9/50.1Gy ± 0.6; R:39.4Gy ± 8.4/47.6Gy ± 4; A:38.3Gy ± 10.4/47.9Gy ± 4.4) and PTV_IMA D95%/D50% (S:37.6Gy ± 3.9/49.7Gy ± 0.8; R:27.9Gy ± 7.8/46.9Gy ± 3.3; A:25.6Gy ± 9.7/47.5Gy ± 2.8). Patient-related dose differences were also significant for OAR`s: Dmean heart (S:4.6Gy ± 1.1; N:6.1Gy ± 1.2; A:7.9Gy ± 2.1), humeral head (S:8.3Gy ± 2.7; N:3.8Gy ± 0.7; A:6.4Gy ± 1.7), and thyroid (S:17.7Gy ± 2.7; N:14.3Gy ± 1.6; A:27.9Gy ± 4.5). Patient anatomical factors and institutional planning differences create significant dosimetric variations in breast cancer radiation therapy, emphasizing the need for personalized planning approaches that incorporate patient-specific constraints and age-dependent risk considerations.
CRIS-Team Scopus Importer:2025-12-26
Keywords: Breast cancer; Lymphatics; RNI